No effect of n-3 fatty acids supplementation on NT-proBNP after myocardial infarction: The Alpha Omega Trial. (29th August 2020) - Hoogeveen, Ellen K; Geleijnse, Johanna M; Kromhout, Daan; van't Sant, Peter; Gemen, Eugenie F; Kusters, Ron; Giltay, Erik J
Abstract: Background: heart failure is a major risk factor for cardiovascular mortality, for which n-3 fatty acids may have beneficial effects. We examined the effect of marine eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and plant-derived alpha-linolenic acid (ALA) on N-Terminal-pro Brain Natriuretic Peptide (NT-proBNP), a biomarker of heart failure. Methods: we randomly assigned 4837 post-myocardial infarction patients, aged 60–80 years (82% men), to margarines supplemented with a targeted additional intake of 400 mg/day EPA and DHA, 2 g/day ALA, EPA-DHA plus ALA, or placebo for 40 months. In a random selection of 639 patients, NT-proBNP was determined both at baseline and at the end of follow-up. NT-proBNP was loge -transformed and analysed by type of treatment using analysis of covariance adjusting for baseline NT-proNBP. Results: patients consumed on average 19.8 g margarine/day, providing an additional amount of 238 mg/day EPA with 158 mg/day DHA, 1.98 g/day ALA, or both, in the active-treatment groups. In the placebo group, the geometric mean level NT-proBNP increased from 245 ng/l (95%-confidence interval [CI]: 207–290) to 294 ng/l (95%-CI: 244–352) after 40 months ( p  = 0.001). NT-proBNP levels were not affected by ALA (+8% versus placebo; 95%-CI: −8% to +25%; p  = 0.34), EPA-DHA (+2% versus placebo; 95%-CI: −14% to +18%; p  = 0.78), nor EPA-DHA plus ALA (+9% versus placebo; 95%-CI: −8% to +25%; p  = 0.31) treatment. Conclusions: supplementation with modest amounts of EPA-DHA, with or without ALA, did not have a significant effect on NT-proBNP levels in patients with a history of myocardial infarction.